The Effect of Intrinsic Motivation, Career Exposure, and Quality of Life on Entrepreneurial Intentions - Dela Hardillah; Tri Hanani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the factors that students consider in choosing a career as an entrepreneur. The three factors that became the focus of observation were intrinsic motivation, career exposure, and quality of life. This study used a quantitative approach. The primary data were obtained through the questionnaire to collect the necessary data. Data collection in this study was carried out at several public and private universities in Mataram City. This study investigates how intrinsic motivation, career exposure, and quality of life influence entrepreneurial intentions. Research findings show that intrinsic motivation has a significant influence on entrepreneurial intentions. Career exposure also positively affects intentions, as it can inspire individuals to pursue entrepreneurial paths. Moreover, quality of life, encompassing well-being, health, and satisfaction, is crucial for fostering entrepreneurial pursuits. These insights can guide policymakers and educators in developing effective entrepreneurship programs and policies.